Influencia del banco de la república en los tipos de cambio en colombia en el período comprendido del año 2008 al año 2019 (2019)
The events that have pointed the evolution of exchange rate policies and exchange rates in Colombia are portrayed in this document, insofar as the Bank of the Republic is understood as the central point and axis of distribution of measures and norms that allow the national market and finances to adapt to the international context and reality. Taking this into account, it is imperative to carry out an evaluation with a period of time between 2008 and 2019 on the influence of the Bank of the Republic on the country's exchange rates based on different macroeconomic data, such as inflation understood as a moderate increase in prices of goods and services. On the other hand, we also talk about GDP and how it relates to the exchange rate; about the institutions or organizations involved in the variation of the data mentioned above and, the different decisions of the bank in that period of time are analyzed to determine whether it influences or not.